Clients’ Experience with FCES: Widespread Satisfaction Tempered with Suggestions for Improvement - Glenn D Israel; Tiffany Henderson (EDIS)
The Florida Cooperative Extension Service (FCES) provides a variety of information to clients throughout the state. In order to determine the extent of client satisfaction, the FCES conducts an annual survey. The survey was sent to a sample of clients who have received educational information between March and July 2017. A total of 1,202 participants responded, and 94.9% of Extension clients reported that they were satisfied or very satisfied with the overall services provided. Many Extension clients also shared suggestions for improving services, including improved communication, increased advertising, and increased availability for some classes. In this five-page document from the UF/IFAS Department of Agricultural Education and Communication, Glenn D. Israel and Tiffany Henderson summarize the results of the survey and provide recommendations for how to improve Extension’s services. http://edis.ifas.ufl.edu/wc326